On a problem of system phenomena in the field of phraseology: the variety of paralinguistic set expressions (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the peculiarities of paralinguistic phrasemes  of the Ukrainian language; the author analyses lexical, grammatical and combined changes in a structure of set phrases and examines the influence of variant components on the  interior formation of a set expression.
Keywords: paralinguistic phraseologism; variety; lexical variations; grammatical variations; combined variations